Transgenic Enrichment of Mouse Embryonic Stem Cell-derived Progenitor Motor Neurons - McCreedy, Dylan A. (2011)
Embryonic stem cells (ESCs) hold great potential for replacing neurons following injury or disease. The therapeutic and diagnostic potential of ESCs may be hindered by heterogeneity in ESC-derived populations. Drug selection has been used to purify ESC-derived cardiomyocytes and endothelial cells but has not been applied to specific neural lineages. In this study we investigated positive selection of progenitor motor neurons (pMNs) through transgenic expression of the puromycin resistance enzyme, puromycin N-acetyl-transferase (PAC), under the Olig2 promoter. The protein-coding region in one allele of Olig2 was replaced with PAC to generate the P-Olig2 cell line. This cell line provided specific puromycin resistance in cells that express Olig2, while Olig2(−) cells were killed by puromycin. Positive selection significantly enriched populations of Olig2(+) pMNs. Committed motoneurons (MNs) expressing Hb9, a common progeny of pMNs, were also enriched by the end of the selection period. Selected cells remained viable and differentiated into mature cholinergic MNs and oligodendrocyte precursor cells. Drug resistance may provide a scalable and inexpensive method for enriching desired neural cell types for use in research applications.